2020
DOI: 10.1186/s12014-020-09276-9
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive systematic review of CSF proteins and peptides that define Alzheimer’s disease

Abstract: Background: During the last two decades, over 100 proteomics studies have identified a variety of potential biomarkers in CSF of Alzheimer's (AD) patients. Although several reviews have proposed specific biomarkers, to date, the statistical relevance of these proteins has not been investigated and no peptidomic analyses have been generated on the basis of specific up-or down-regulation. Herein, we perform an analysis of all unbiased explorative proteomics studies of CSF biomarkers in AD to critically evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 122 publications
8
56
0
Order By: Relevance
“…Unbiased or large-scale targeted proteomic CSF analyses have potential to further refine which biological processes become disrupted in Alzheimer’s disease. So far, Alzheimer’s disease proteomic studies mostly focussed on finding novel biomarkers by comparing patients with Alzheimer’s disease with control subjects ( Maarouf et al , 2009 ; Meyer et al , 2018 ; for reviews see Pedrero-Prieto et al , 2020 ; Wesenhagen et al , 2020 ), and so it remains unclear whether pathophysiological subtypes within Alzheimer’s disease can be discovering with CSF proteomics. Furthermore, if genetic variance in Alzheimer’s disease risk genes contributes to interindividual variability in underlying disease mechanisms, it can be hypothesized that these should already be detectable in presymptomatic stages of Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Unbiased or large-scale targeted proteomic CSF analyses have potential to further refine which biological processes become disrupted in Alzheimer’s disease. So far, Alzheimer’s disease proteomic studies mostly focussed on finding novel biomarkers by comparing patients with Alzheimer’s disease with control subjects ( Maarouf et al , 2009 ; Meyer et al , 2018 ; for reviews see Pedrero-Prieto et al , 2020 ; Wesenhagen et al , 2020 ), and so it remains unclear whether pathophysiological subtypes within Alzheimer’s disease can be discovering with CSF proteomics. Furthermore, if genetic variance in Alzheimer’s disease risk genes contributes to interindividual variability in underlying disease mechanisms, it can be hypothesized that these should already be detectable in presymptomatic stages of Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Additional rare polymorphisms have been identified in patients suffering from late onset AD, in which secreted clusterin levels are reduced due to folding abnormalities ( Bettens et al, 2015 ). Six independent proteomics studies show that CSF levels of clusterin are significantly increased in AD patients (see meta-analysis in Pedrero-Prieto et al, 2020 ); plasma levels also rise in ALS ( Xu et al, 2018 ). Additionally, while brain clusterin levels increase within the brain during AD progression, the levels of Abeta increase to a greater extent, resulting in a declining molar ratio between clusterin and Abeta specifically within regions of the brain with high Abeta deposition ( Miners et al, 2017 ).…”
Section: Clusterinmentioning
confidence: 99%
“…Immunofluorescence studies have similarly shown that proSAAS co-localizes with aggregated proteins involved in neurodegenerative disease, namely tau tangles in dementia ( Kikuchi et al, 2003 ); Abeta plaques in AD ( Hoshino et al, 2014 ); and Lewy bodies in PD ( Helwig et al, 2013 ). Seven independent proteomics studies have shown that the level of proSAAS in CSF taken from AD and/or FTD patients is reduced as compared to controls, suggesting possible cellular retention within the brain ( Davidsson et al, 2002 ; Abdi et al, 2006 ; Finehout et al, 2007 ; Jahn et al, 2011 ; Choi et al, 2013 ; Holtta et al, 2015 ; Spellman et al, 2015 ; reviewed in Pedrero-Prieto et al, 2020 ). Two very recent CSF studies support this reduction ( Rotunno et al, 2020 ; Van Steenoven et al, 2020 ).…”
Section: B2 and Prosaasmentioning
confidence: 99%
See 2 more Smart Citations